one new species of the genus Thottea Tottb. (Aristolochiaceae Juss.) for the flora of Vietnam - Huyen, Duong Duc (Academia Journal of Biology, 2014)
Up to our paper, Thottea hainanensis (Merr. & Chun) Ding Hou (Aristolochiaceae) was considered as an endemic species of Hainan (China). During our examination of the specimens numbered VN 1441 collected by Nguyen Quoc Binh on 21 January 2005 in Quangtri province (Dac-Krong) and kept in the herbarium of the Institute of Ecology and Biological resources in Hanoi (HN), we have identified that they belong to the species Thottea hainanensis, a new record for the flora of Vietnam.